1986
DOI: 10.1159/000132266
|View full text |Cite
|
Sign up to set email alerts
|

Human ornithine decarboxylase sequences map to chromosome regions 2pter→p23 and 7cen→qter but are not coamplified with the NMYC oncogene

Abstract: Using a mouse cDNA probe for ornithine decarboxylase (ODC), we have identified and isolated an ODC cDNA clone from a λ gt11 recombinant library prepared from human liver cell mRNA. The 2.0-kb insert of this clone hybridizes with several mouse genomic ODC DNA restriction fragments under conditions of low stringency, but reacts with only few human DNA fragments and a polyA+ RNA species of 2.2 kb under both nonstringent and stringent hybridization conditions. This suggests that, unlike the mouse genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Zimmerman et al [4] and Vriese et al [5] found increased peritoneal permeability in diabetic rats. An increase in peritoneal permeability to protein in DM patients was revealed by Krediet et al [6]. Due to increasing numbers of DM patients on continuous ambulatory peritoneal dialysis, we designed a study to clarify this issue, paying particular attention to UF rate in DM and non-DM patients.…”
Section: Introductionmentioning
confidence: 94%
“…Zimmerman et al [4] and Vriese et al [5] found increased peritoneal permeability in diabetic rats. An increase in peritoneal permeability to protein in DM patients was revealed by Krediet et al [6]. Due to increasing numbers of DM patients on continuous ambulatory peritoneal dialysis, we designed a study to clarify this issue, paying particular attention to UF rate in DM and non-DM patients.…”
Section: Introductionmentioning
confidence: 94%
“…In each case, however, only one of several genomic fragments that hybridize with the homologous Or/ccDNA probe is amplified (McConlogue etal., 1984;Winquist et al, 1986). The fact that the amplified fragments are derived from conserved regions of human chromosome 2 and mouse chromosome 12 provides additional evidence that they represent functional Ode loci in man and mouse, since the chromosomal location of pseudogenes is not nor mally conserved over evolution.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of the physical proximity of the NMYC and ODC genes on human chromosome 2, ODC is not amplified along with NMYC in human tumors nor does 2-difluoromethyl ornithine selection cause amplification of NMYC along with ODC (Winquist et al, 1986). Since the amplified chromosomal material in I MR-32 tumor cells is estimated to be ~3,000-kb (Shiloh et al, 1985), the ODC and NMYC genes on human chromosome 2 are likely to be quite far apart in molecular terms.…”
Section: Discussionmentioning
confidence: 98%
“…The DNA was digested with restriction enzymes according to the instruction of the suppliers. The restriction fragments were electrophoresed in 0.9% agarose gels, transferred to nitrocellulose filters [10] and hybridized with nick-translated [11] pODC10/2H complementary to the human ODC mRNA [12]. The specific activity of the probe was 1 × 10 s cpm//zg.…”
Section: Preparative and Analytical Methodsmentioning
confidence: 99%